Diagnostic and Treatment Patterns in Management of Male Patients with Nongonococcal Urethritis: Results of Russian Multicentral Cross-Sectional Study - I. V. Andreeva; S. N. Kozlov; S. V. Korolev; A. N. Belikov; A. V. Grinev; V. V. Evstafiev; N. N. Kirpicheva; M. V. Serdyutskaya; O. U. Stetsyuk; A. A. Fokin; A. A. Khryanin (Антибиотики и Химиотерапия, 2020)
The aim of the study was to estimate the diagnostic and treatment patterns in the management of acute nongonococcal urethritis (NGU) in males in some cities of Russia. Retrospective cross-sectional study was conducted in 2009 in 5 centers of 4 cities in the _ Central Part of Russia (Kaluga, Pskov, Smolensk - 2 cen- tres and Tula). The data on the diagnostic and treatment approaches to the management of NGU in male subjects >16 years old were collected and analyzed with the use of special ly designed case report forms. 556 cases of acute urethritis were analyzed during the study. The diagnosis of NGU was confirmed in 401 cases. The average age of the patients was 29.8 years (16-68 years). The following diagnostic methods were used in 95% of the cases: urethral smear microscopy (314/82.4%), C.trachomatis - PCR (113/29.7%), ELISA (155/40.7%); T.vaginalis - PCR (106/27.8%); U.urealyticum and M.hominis, respectively - bacteriology (140/36.7% and 126/33.1%), PCR (110/28.9% and 108/28.3%); M.genitalium - PCR (110/28.9%). The treatment patterns included antimicrobials AMs alone in 60.3, and AMs + non-AMs in 37.8% of the cases. The most frequently prescribed AMs were azithromycin (27.5%), fluconazole (16.4%), doxycycline (13.6%), metronidazole (11.2%), of loxacine (7.3%), ceftriaxone (4.4%), josamycin (4.2). According to the results use of the standard methods for NGU diagnosis was rather rare. The use of PCR for atypical pathogens was the following: C.trachomatis 29.7%, U.urealyticum 36.7%, M.hominis 28.9%, M.genitalium 28.3%. Doubtful culture methods were used for detection of U.urealyticum and M.hominis (36.7% and 33.1%). The AMs treatment in some cases was not in compliance with the up-to-date practical guidelines for STD and NGU.